UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MELALUI METODE SAS SISWA KELAS 1 SDN GALENGDOWO 2 WONOSALAM - Adib Jion Satriyo (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research was conducted to overcome the problem of the low reading ability of students at SD Negeri Galengdowo 2 Wonosalam. Therefore the researchers made efforts to improve students' reading skills through the SAS method. This research involved 36 students of SD Negeri Galengdowo 2 Wonosalam. The design of this research is classroom action research. From the research results, it was obtained that the average value in cycle I was 69.44% of 36 grade 1 students at SD Negeri Galengdowo 2 Wonosalam. Whereas in cycle II the learning completeness that has been achieved classically is 91.66%.